The economic research potentials of the German Socio-Economic Panel study - Carsten Schröder; Johannes König; Alexandra Fedorets; Jan Goebel; Markus M. Grabka; Holger Lüthen; Maria Metzing; Felicitas Schikora; Stefan Liebig (German Economic Review, 2020)
We provide a concise introduction to a household-panel data infrastructure that provides the international research community with longitudinal data of private households in Germany since 1984: the German Socio-Economic Panel (SOEP). We demonstrate the comparative strength of the SOEP data in answering economically-relevant questions by highlighting its diverse and impactful applications throughout the field.
Keywords: C2; C3; C5; C8; D04; D1; D3; D6; D7; D9; I00; J1; J2; J3; J6; 330; panel data; Socio-Economic Panel; inequality; policy evaluations; wellbeing; health; education; demographic economics; labor economics; wages; mobility; migration; behavioral economics; experiments